ANALISIS PENGARUH NPM, PER DAN PBV TERHADAP HARGA SAHAM SYARIAH DI BURSA EFEK INDONESIA (PENELITIAN DI PT. ANEKA TAMBANG TBK. PERIODE JANUARI 2018 - MARET 2021) - Taufik, Hilman; Jalaludin, Jalaludin (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2022)
The number of investors in the Indonesian Capital Market has continued to experience a very high increase in recent years. These investors are dominated by investors with a high school education level, which is around 52.94%. This research is motivated by the rapid increase and decrease in stock prices, so it is necessary to study what factors can be used as a benchmark for increasing or decreasing the stock price. Researchers analyze the relationship that may occur from the ratios of financial statements to stock prices. The financial report ratios studied included Net Profit Margin (NPM), Price Earning Ratio (PER) and Price to Book Value (PBV). The purpose of this study was to determine the effect of NPM on PT Aneka Tambang Tbk's sharia share price, the effect of PER on PT Aneka Tambang Tbk's sharia share price, the effect of PBV on PT Aneka Tambang Tbk's sharia share price and the effect of NPM, PER and PBV on PT Aneka Tambang Tbk's sharia share price. Aneka Tambang Tbk. The research method used is multiple linear regression with a quantitative approach. This research was conducted based on Antam's financial report data and share prices from January 2018 to March 2021 which were taken on the official website of IDX / Aneka Mining Company. The results of this study can be concluded that first the NPM financial ratio has no influence on Antam's stock price seen from the results of the t-test a significance value of more than 0.05 which is equal to 0.520, secondly the PER financial ratio has no influence on Antam's share price seen from the results of the test- t a significance value of more than 0.05 which is equal to 0.594, the third PBV financial ratios have an influence on Antam's share price seen from the results of the t-test the significance value is not more than 0.05 which is equal to 0.000, the four financial ratios NPM, PER and PBV have an influence very significant to Antam's share price seen from the results of the f-test the significance value is not more than 0.05 which is equal to 0.000 with a significance level of 98.6%.